Personal Strategies for DIEP Flap Breast Reconstruction in Patients with Prior Abdominal Surgery and Hernia Repairs - Gupta, Samarth; Arora, Rajan; Mishra, Kripa; Kumar, Anchit; Prasad, Nikhil (Archives of Plastic Surgery)
Delayed breast reconstruction using deep inferior epigastric perforator (DIEP) flaps in patients with a history of abdominal wall hernias and/or cesarean sections presents unique challenges. This study examines 10 such cases, emphasizing key technical considerations. Our findings highlight the importance of lateral row perforators, as medial paraumbilical perforators are often compromised in patients with prior umbilical hernia repairs. Additionally, deep inferior epigastric arteries (DIEAs) may be damaged in previous lower abdominal surgeries, necessitating intraoperative confirmation of vessel patency. While preoperative CT angiography aids in planning, it may misrepresent perforator size or location due to adherence to fascia. In our approach, a gastrointestinal (GI) surgeon performed concurrent hernia repair while the plastic surgery team secured the DIEP flap perforators and pedicle. Preservation of umbilical vascularity was ensured by avoiding complete skeletonization. In the case shown, only a single lateral row perforator was usable, despite preoperative imaging suggesting additional perforators. All patients had successful flap integration, with no cases of flap failure, necrosis, postoperative hernias, wound dehiscence, seroma, hematoma, or infection. Delayed flap inset was performed using the Rosebud technique, ensuring optimal aesthetic outcomes and high patient satisfaction. This study highlights the critical role of a multidisciplinary approach, precise perforator identification, and careful interpretation of preoperative imaging in achieving optimal outcomes in complex DIEP flap breast reconstruction.